Perjuangan Menuju Keselamatan Kekal: Memahami Kasih Karunia dalam Yesus Kristus Menurut Perspektif Efesus 2:8-10 - Hendrikson Febri (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
Grace (charis) means unmerited favor or goodness. Grace can take simple forms, such as forgiving someone who has done wrong or offering help to those in need. Additionally, grace is the opportunity given to humanity to attain eternal salvation. The research question in this study is: how is the struggle towards salvation through grace in Jesus Christ according to the perspective of Ephesians 2:8-10? Therefore, the aim of this study is to understand the struggle towards salvation through grace in Jesus Christ. The research method used in this study is a qualitative approach with a hermeneutic method, to understand and interpret the meaning of grace in Jesus Christ as explained in Ephesians 2:8-10. The results of this study indicate that Ephesians 2:8-10 affirms that the journey towards eternal salvation is the result of God's sovereign grace, which transforms the identity and purpose of believers, enabling them to be instruments to glorify God's name while on this earth.